BIOECONOMY-BASED FOOD INDUSTRY OF SERBIA: THE ROLE OF INTELLECTUAL CAPITAL - Dobrijević, Gordana; Đorđević Boljanović, Jelena; Đoković, Filip; Pejanović, Radovan; Škatarić, Goran; Damnjanović, Ivana (Economics of Agriculture, 2019)
The aim of this exploratory study was to determine most useful indicators of intellectual capital in Serbian food industry. The study investigated managers perceptions of indicator usefulness and practical application. They were top and middle managers from 18 food organizations, committed to the bioeconomy. The survey items were divided into human, structural, and relational capital. A closed-ended questionnaire was used to collect data, later analysed by SPSS 21 statistical software. The results have demonstrated that all indicators were seen as very important, with relational capital being the most useful of all.